Synthesis and structural characterization of monomeric and dimeric peptide nucleic acids prepared by using microwave-promoted multicomponent reactions. Issue 45 (23rd September 2015) - Ovadia, Reuben; Lebrun, Aurélien; Barvik, Ivan; Vasseur, Jean-Jacques; Baraguey, Carine; Alvarez, Karine
Abstract : A solution phase synthesis of peptide nucleic acid monomers and dimers was developed by using microwave-promoted Ugi multicomponent reactions. Abstract : A solution phase synthesis of peptide nucleic acid monomers and dimers was developed by using microwave-promoted Ugi multicomponent reactions. A mixture of a functionalized amine, a carboxymethyl nucleobase, paraformaldehyde and an isocyanide as building blocks generates PNA monomers which are then partially deprotected and used in a second Ugi 4CC reaction, leading to PNA dimers. Conformational rotamers were identified by using NMR and MD simulations.